The Effect of Yttrium Addition on the Microstructures and Electrical Properties of CuMn Alloy Thin Films - Ho-Yun Lee; Chi-Wei He; Ying-Chieh Lee (Advances in Materials Science and Engineering)
In this study, we fabricated thin-film resistors using CuMn and yttrium targets by DC/RF magnetron cosputtering. CuMnY-resistive thin films were deposited onto glass and Al2O3 substrates. The electrical properties and microstructures of CuMn alloy films with different yttrium content were investigated. The CuMnY films were annealed at temperature ranging from 250°C to 350°C in N2 atmosphere. The phase variation, microstructure, film thickness, and constitutional analysis of CuMnY films were characterized using X-ray diffraction, field emission scanning, and high-resolution transmission electron microscopy and related energy dispersive X-ray analyses (XRD, FESEM, and HRTEM/EDX). It was found that CuMnY alloy films separated into two parts after annealing. The first part is the MnO phase on the bottom side of the film. The second part is an amorphous structure on the upper side of the film. The MnO phase is a microcrystalline that exists in CuMn films, which is dependent on the Y content and annealing temperature. CuMn alloy films with 15.7% yttrium addition annealed at 300°C exhibited higher resistivity ∼4000 μΩ-cm with −41 ppm/°C of temperature coefficient of resistance (TCR).